Nut Consumption and Renal Function Among Women at High Risk (FS10-05-19). (13th June 2019) - Ajjarapu, Aparna; Hinkle, Stefanie; Wu, Jing; Li, Mengying; Rawal, Shristi; Chen, Liwei; Mills, James; Pitsava, Georgia; Bjerregaard, Anne; Grunnet, Louise; Zhu, Yeyi; Francis, Ellen; et al.
Abstract: Objectives: Women with gestational diabetes (GDM) are at increased risk for renal complications later in life. Nut intake has been associated with reduced cardiometabolic risk, but few studies have examined its association with renal function. We examined associations of nut intake and renal function among women with prior GDM. Methods: We studied 330 women from the Danish National Birth Cohort (1996–2002) with a GDM pregnancy who participated in a clinical exam 9 to 16 years after the index pregnancy as part of the Diabetes & Women's Health Study (2012–2014) and were free of major chronic diseases at follow-up. Habitual past year intake of nine types of nuts was ascertained at follow-up using a food frequency questionnaire. Total nut intake was classified as none (<1 serving/mo), monthly (2–3 servings/mo), weekly (1–6 servings/wk), and daily (>1 serving/d). Estimated glomerular filtration rate (eGFR) via CKD-EPI equation and urine albumin-to-creatinine ratio (UACR) were calculated based on serum creatinine (mg/dL) and urine albumin (mg/L), and creatinine (mg/dL) measurements respectively. We estimated % differences with 95% confidence intervals (CI) in these outcomes by nut intake adjusted for current body mass index, age, physical activity, energy intake, and dietary variables. We explored possible non-linear relations using restricted cubic splines. Results: A significant non-linear U-shaped association was detected between total nut consumption and UACR ( P  = 0.001) with lowest UACR levels among women with weekly consumption. Compared to women with weekly intake ( n  = 222), adjusted UACR levels were 86% [95% CI: 15%, 200%] and 23% [−1%, 54%] higher among women with no or monthly nut intake, respectively, while UACR levels were 118% [22%, 286%] higher among women with daily intake. Compared to weekly consumers, adjusted eGFR levels were 9% [0%, 19%] higher among daily consumers. Conclusions: Moderate nut consumption may be beneficial to kidney health among women with prior GDM. Funding Sources: Intramural Research Program of the NICHD, March of Dimes Birth Defects Foundation, Innovation Fund Denmark, Health Foundation, Heart Foundation, EU, Danish Diabetes Academy supported by Novo Nordisk Foundation, and NIH Building Interdisciplinary Research Careers in Women's Health Program.